ANALISIS PENGUNGKAPAN INTERNET FINANCIAL REPORTING PERUSAHAAN ASURANSI-PERBANKAN SYARIAH DI INDONESIA-MALAYSIA - Ilham Maulana Saud; Bustanul Ashar; Peni Nugraheni (Media Riset Akuntansi, Auditing & Informasi, 2019)
This study aims to find empirical evidence related to the influence of leverage, auditor reputation, efficiency, growth, internationalization and board of commissioner's level of Internet Financial Reporting. The population in this study are all sharia-based companies in Indonesia and Malaysia. Sampling using purposive sampling method and obtained sample of 66 company data in Indonesia and 73 company data in Malaysia. Data analyzed in this research is processed from annual report and company financial statements and analysis techniques used in this research is multiple regression analysis using SPSS version 24. The results of this study indicate that in Indonesia, the reputation of auditors and internationalization has a positive and significant impact on Internet Financial Reporting while leverage, efficiency, growth and education level of board of commissioners have no significant effect on internet financial reporting. In Malaysia the reputation of auditors, growth and internationalization have a positive and significant impact on internet financial reporting while leverage, efficiency and education level of board of commissioner have no significant effect to internet financial reporting.